2001
DOI: 10.1080/00150190108016255
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of ferroelectric Ba1−xSrxTiO3thin films for room temperature tunable microwave devices

Abstract: This paper will review the recent progress of the Texas Center for Superconductivity concerning the epitaxial growth of ferroelectric Bal-,Sr,Ti03 thin films on various substrates using pulsed laser ablation. Microstructure studies from X-ray diffraction and electron microscopy suggest that the as-grown films on (001) LaAIO, and (001) MgO are c-axis oriented with excellent single crystallinity. The Rutherford Back-Scattering Spectroscopic studies indicate that the films have excellent epitaxial behavior. Micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This was confirmed by the rocking measurements from the (001) reflections of the BST films deposited on (001) LAO and (001) MgO substrates at almost the same growth conditions. 56 The value of the full-width at half-maximum (FWHM) was measured to be less than 0.15°for the film on (001) LAO, but was about 0.3°for the BST film on MgO. The smaller FWHM value for the BST film on (001) LAO indicates that the as-grown BST film on LAO has a better single-crystallinity quality than that of BST films on MgO.…”
Section: Interfacial Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…This was confirmed by the rocking measurements from the (001) reflections of the BST films deposited on (001) LAO and (001) MgO substrates at almost the same growth conditions. 56 The value of the full-width at half-maximum (FWHM) was measured to be less than 0.15°for the film on (001) LAO, but was about 0.3°for the BST film on MgO. The smaller FWHM value for the BST film on (001) LAO indicates that the as-grown BST film on LAO has a better single-crystallinity quality than that of BST films on MgO.…”
Section: Interfacial Structuresmentioning
confidence: 98%
“…Such strain energy also makes it difficult to grow high-quality epitaxial BST films on MgO substrates. Chen et al 56,57 and Gao et al 58 have examined the interface behavior of the epitaxial (Ba 0.6 Sr 0.4 )TiO 3 films on the (001) MgO and (001) LAO substrates by using x-ray diffraction and electron microscopy. Their results showed that the asgrown film has a high degree of crystallinity and good in-plane orientation: <100> BST //<100> MgO and (100) BST //(100) MgO , as confirmed by x-ray diffraction and selected-area electron diffraction patterns.…”
Section: Interfacial Structuresmentioning
confidence: 99%
“…However, the large dielectric loss and the large dielectric constants (>1000) become the road block for tunable device developments. 3,[5][6][7][8][9] Recently, thin film of a nonferroelectric material, (Bi 1.5 Zn 0.5 )(Zn 0.5 Nb 1.5 )O 7 (BZN), with a cubic A 2 B 2 O 7 pyrochlore structure, displays very low dielectric loss ($5 Â 10 À4 ) and a medium permittivity (170-200) which can be tuned by the applied voltage. [10][11][12] In terms of physics, the cubic pyrochlore structure can tolerate considerable Zn substitution on the A site, and the inhomogeneous distribution of Zn 2þ atoms and vacancies on the Bi 3þ sites is demonstrated to enhance the additional random fields, rendering the multiwall potentials to be widely distributed in heights, and associated transition rates for Bi 3þ and Zn 2þ cations.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] For example the dielectric tunability is larger for (111) oriented films compared to (001) and the best electrical properties are obtained on (001) epitaxial BST films. 11,12 In this context, it is important to compare the structural and the microstructural properties of BST films exhibiting (001) and (111)-preferred orientations, as fiber-or epitaxial textures. The residual stresses in the films, which are certainly different between films differently oriented, have also a non-negligible effect on the films tunability.…”
Section: Introductionmentioning
confidence: 99%